Effects of ocean acidification increase embryonic sensitivity to thermal extremes in Atlantic cod, Gadus morhua. (1st November 2016) - Dahlke, Flemming T.; Leo, Elettra; Mark, Felix C.; Pörtner, Hans‐Otto; Bickmeyer, Ulf; Frickenhaus, Stephan; Storch, Daniela
Abstract: Thermal tolerance windows serve as a powerful tool for estimating the vulnerability of marine species and their life stages to increasing temperature means and extremes. However, it remains uncertain to which extent additional drivers, such as ocean acidification, modify organismal responses to temperature. This study investigated the effects of CO2 ‐driven ocean acidification on embryonic thermal sensitivity and performance in Atlantic cod, Gadus morhua, from the Kattegat. Fertilized eggs were exposed to factorial combinations of two P CO2 conditions (400 μ atm vs. 1100 μ atm) and five temperature treatments (0, 3, 6, 9 and 12 °C), which allow identifying both lower and upper thermal tolerance thresholds. We quantified hatching success, oxygen consumption ( M O2 ) and mitochondrial functioning of embryos as well as larval morphometrics at hatch and the abundance of acid–base‐relevant ionocytes on the yolk sac epithelium of newly hatched larvae. Hatching success was high under ambient spawning conditions (3–6 °C), but decreased towards both cold and warm temperature extremes. Elevated P CO2 caused a significant decrease in hatching success, particularly at cold (3 and 0 °C) and warm (12 °C) temperatures. Warming imposed limitations to M O2 and mitochondrial capacities. Elevated P CO2 stimulated M O2 at cold and intermediate temperatures, but exacerbated warming‐induced constraints on M O2, indicating a synergistic interaction with temperature. Mitochondrial functioning was not affected by P CO2 . Increased M O2 in response to elevated P CO2 was paralleled by reduced larval size at hatch. Finally, ionocyte abundance decreased with increasing temperature, but did not differ between P CO2 treatments. Our results demonstrate increased thermal sensitivity of cod embryos under future P CO2 conditions and suggest that acclimation to elevated P CO2 requires reallocation of limited resources at the expense of embryonic growth. We conclude that ocean acidification constrains the thermal performance window of embryos, which has important implication for the susceptibility of cod to projected climate change.